A Theory of Multiperiod Debt Structure - Huang, Chong; Oehmke, Martin; Zhong, Hongda (Review of Financial Studies, 2019)
[We develop a theory of multiperiod debt structure. A simple trade-off between the termination threat required to make debt repayments incentive compatible and the desire to avoid early liquidation determines the number of repayments, their timing, and amounts. As firms increase their borrowing, they add periodic risky repayments from the back of the maturity structure, with the time between repayments increasing in cash-flow risk. Cash-flow growth or a significant risk-free cash-flow component limits the number of risky repayments. Firms with a significant risk-free cash-flow component choose dispersed maturity profiles with smaller, relatively safe repayments every period, rather than riskier periodic repayments.]